Updates on Pancreatic Cancer - Highlights from the “48th Annual Pancreas Club Meeting”. Chicago, IL, USA. May 2-3, 2014 - Vyas, Ojas; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
No abstract available. Image: Chicago view. (From the Program of the "48th Annual Pancreas Club Meeting. Chicago, IL, USA. May 2-3, 2014).